Green synthesis of carbon- and silver-modified hierarchical ZnO with excellent solar light driven photocatalytic performance - Shen, Z.; Liang, P.; Wang, Shaobin; Liu, Lihong; Liu, Shaomin (American Chemical Society, 2015)
Superstructured ZnO has been the focus of intensive study due to its promising diverse applications. Here, we demonstrate a facile synthesis of hierarchical ZnO particles hybridized with carbon and silver via a simplified bioprocess using yeast mold broth. Better than traditional microbial and biomimetic methods, our microbe-free strategy offers superior ease-of-preparation with minimal negative environmental impact. The relevant reaction parameters including zinc precursor concentration, broth pH value, and broth content were systemically investigated to control the particle morphologies from solid microrod to mesocrystals of porous microcylinder, nanodisk, nanocone, nanoflower, and microhamburger. Silver nanoparticles were facilely deposited by photoreduction in the broth. The resultant ZnO@C–Ag composite exhibits a significant improvement in the solar light-irradiated photodegradation of methylene blue solution.